The effect of combination of aerobic and strengthening exercise on muscle strength, balance, and sleep quality in individuals with type 2 diabetes - Yılmaz Menek, Merve; Budak, Miray (Duzce University Medical School, 2022)
Aim: The aim of this study was to determine the effects of aerobic and strengthening exercise combination on glycosylated hemoglobin (HbA1c), muscle strength, balance, and sleep quality in individuals diagnosed with type 2 diabetes mellitus (DM). Material and Methods: Fifty individuals aged between 30 and 65 years and diagnosed with type 2 DM were included in this study. Anthropometric measurements, HbA1c, quadriceps and hamstring muscle strength, balance, and sleep quality of the included individuals were evaluated. Aerobic and strengthening exercises were applied to the participants 3 days a week for 12 weeks. All evaluation measurements were repeated at the end of 12 weeks. Results: Of the 50 individuals included in this study and diagnosed with type 2 DM, 64% (n=32) were male and 36% (n=18) were female. The mean age of the participants was 50.12±10.81 years, the mean body mass index was 29.97±3.12 kg/m2, the waist/hip ratio was 0.91±0.08, and the mean HbA1c was 9.19±2.39. When the pre and post-treatment HbA1c, muscle strength, balance, and sleep quality measurements of all participants were compared, there were statistically significant differences (p<0.001). Conclusion: It was determined that the combination of long-term aerobic and strengthening exercise decreased the HbA1c value and also significantly improved muscle strength, balance, and sleep quality in individuals with type 2 DM. A structured exercise program that includes strengthening and aerobic exercises would be beneficial in developing the most effective and appropriate exercise prescriptions in terms of exercise efficiency and sustainability for individuals with type 2 DM.

Amaç: Bu çalışmanın amacı, tip 2 diabetes mellitus (DM) tanısı olan bireylerde aerobik ve kuvvetlendirme egzersiz kombinasyonunun glikozile hemoglobin (HbA1c), kas kuvveti, denge ve uyku kalitesi üzerine etkilerini belirlemektir. Gereç ve Yöntemler: Bu çalışmaya 30 ve 65 yaş arası ve tip 2 DM tanısı olan 50 birey dahil edildi. Dahil edilen bireylerin antropometrik ölçümleri, HbA1c, quadriseps ve hamstring kas gücü, denge ve uyku kalitesi değerlendirildi. Katılımcılara 12 hafta boyunca haftada 3 gün aerobik ve kuvvetlendirme egzersizleri uygulandı. Tüm değerlendirme ölçümleri 12 haftanın sonunda tekrar edildi. Bulgular: Bu çalışmaya dahil edilen ve tip 2 DM tanısı olan 50 bireyin %64'ü (n=32) erkek ve %36'sı (n=18) kadın idi. Katılımcıların yaş ortalaması 50,12±10,81 yıl, ortalama beden kitle indeksi 29,97±3,12 kg/m2 , bel/kalça oranı 0,91±0,08 ve ortalama HbA1c değeri 9,19±2,39 idi. Tüm katılımcıların tedavi öncesi ve tedavi sonrasındaki HbA1c, kas gücü, denge ve uyku kalitesi ölçümleri karşılaştırıldığında istatistiksel olarak anlamlı farklar vardı (p<0,001). Sonuç: Tip 2 DM olan bireylerde uzun süreli aerobik ve kuvvetlendirme egzersizi kombinasyonunun HbA1c değerini azalttığı ve ayrıca kas gücü, denge ve uyku kalitesini de önemli ölçüde iyileştirdiği belirlendi. Kuvvetlendirme ve aerobik egzersizleri içeren yapılandırılmış bir egzersiz programı, tip 2 diyabet olan bireyler için egzersiz etkinliği ve sürdürülebilirliği açısından en etkili ve uygun egzersiz reçetelerinin geliştirilmesinde faydalı olacaktır.
Tip 2 diyabet olan bireylerde aerobik ve kuvvetlendirme egzersiz kombinasyonunun kas gücü, denge ve uyku kalitesi üzerine etkisi
Keywords: Aerobic Exercise; Balance; Muscle Strength; Strengthening Exercises; Type 2 Diabetes; Aerobik Egzersiz; Denge; Kas Gücü; Kuvvetlendirme Egzersizleri; Tip 2 Diyabet